Study on the mechanism of advanced grouting reinforcement in fault fractured zones of deep large-mining-height fully mechanized mining faces - Weng, Mingyue; Du, Bin; Zhang, Yuan; Zhu, Lingjin; Wan, Zhijun; Fan, Bowen; Guo, Hao (Frontiers in Earth Science, 2025)
Aiming at the problem of poor control over coal wall spalling and roof instability when large-mining-height working faces in deep mines pass through fault fractured zones, this study takes the fault fractured zone in the 7,436 working face of Kongzhuang Coal Mine as the engineering background. Through experimental testing of different grouting materials for material optimization, numerical simulation of grout diffusion laws in the fracture network of fault zones, and industrial trials of advanced grouting reinforcement, the directional regulation mechanism of grouting hole spatial layout parameters on grout seepage in fault fractured zones is revealed. The results show that Jumina ultra-fine cement achieves an optimal balance among rheological properties, mechanical characteristics, and economic efficiency. When grouting holes are vertically positioned within 1.0 m above the coal seam, bidirectional grout diffusion into the coal seam and roof is realized, reducing the risk of grout leakage in the fault zone. When grouting holes horizontally extend more than 2 m beyond the fault, the grout diffusion range expands, with the proportions of grouting volume and seepage length in the fault zone decreasing to 34% and 30%, respectively, achieving the best seepage effect. Orthogonal tests identify a water-cement ratio of 0.6 and a grouting pressure of 15 MPa as the optimal parameter combination. Industrial trials confirm that after implementing the optimized grouting scheme, spalling and roof collapse phenomena are significantly reduced, and the working face advancing rate is increased from 1 cycle every 2 days to 2–3 cycles per day, greatly improving working face production efficiency.